Women and advocacy: study of the Ahmadiyya community in Tasikmalaya - Inasshabihah Inasshabihah (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
Advocacy against Ahmadiyya Indonesian Congregation (JAI) has been carried out in Tasikmalaya, West Java, both internally and externally to resolve various forms of intolerance, including mosques sealing and marriage registration. This research highlights the contribution of Ahmadi women with their experiences and efforts in the advocacy process through the concept of Agency and advocacy based on two approaches: Rights and Social Inclusion. This research shows that, 1) the experience of being a victim of intolerance is able to transform women from objects into subjects of advocacy and play a role in advocating themselves and their groups, and 2) internal advocacy is important to provide legal understanding to survivors to increase the awareness of Rights within groups. Therefore, women can contribute positively to the ongoing advocacy works.